2011
DOI: 10.1088/0957-4484/22/23/235701
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hybrid structures: copper oxide nanocrystals templated on ultralong copper nanowires for open network sensing at room temperature

Abstract: A facile large-scale synthesis approach for producing intrinsically p-type nanowires with uniform coverage of nanocrystals to form a highly interconnected porous nanowire network is of great demand for p-type sensing. Here, we have demonstrated synthesis of a very high aspect ratio (10(2)-10(5)) open network of interconnected hybrid nanocrystals-nanowire copper and copper oxide nanomaterials. The copper nanowire scaffold is employed to realize a porous and highly interconnected network of hybrid metal-metal ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 24 publications
0
37
0
1
Order By: Relevance
“…When an excess of laser energy is applied to the mixed CuO/NiO NPs, the reduced Cu and Ni become reoxidized. Temperatures above 673 K lead Cu to form CuO [ 8 , 17 ]. In this case, composite metal oxide micropatterns are formed.…”
Section: Discussionmentioning
confidence: 99%
“…When an excess of laser energy is applied to the mixed CuO/NiO NPs, the reduced Cu and Ni become reoxidized. Temperatures above 673 K lead Cu to form CuO [ 8 , 17 ]. In this case, composite metal oxide micropatterns are formed.…”
Section: Discussionmentioning
confidence: 99%
“…At a certain elevated temperature, the oxide layer starts to form through the grain boundaries and defects of the Cu NWs. A thin sheath of Cu 2 O formed on the Cu‐NW surface as a result . The Cu ion consequently moves from the inner side of the Cu NW to the Cu 2 O/O 2 boundary, while O 2 diffuses into the NW.…”
mentioning
confidence: 99%
“…Figure 4 a shows the computing temperature profiles at the center of the focused laser spot, using FEM. The profile illustrates that the laser-induced temperature can be increased to 250 °C at a 5 mm s −1 scanning speed, with a power of 3 W. This temperature is lower than the 350 °C, at which Cu is oxidized [ 20 , 45 ]. It has been demonstrated that the thermal decomposition temperature of Cu(OH)(NO 3 ) is higher than 238 °C [ 25 , 46 ].…”
Section: Resultsmentioning
confidence: 99%